Principles of Teaching Foreign Languages (Texas Journal of Multidisciplinary Studies, 2022)
The learning process is very voluminous and multifaceted. It is hard to imagine that all principles can be relevant for the whole process. Under the principles of learning, it is customary to consider the main provisions that determine the nature of the learning process, which are formed on the basis of the chosen direction and approaches corresponding to this direction. Clearly formulated learning principles will help decide. Foreign methodologists note the importance of linguistic, psychological and didactic factors in teaching a foreign language, however, the concept of "learning principle" is not a basic category of foreign methodology and is currently rarely found in publications, probably due to the fact that the term itself implies the dominant role of the teacher in educational process, which is rejected by modern methodologists.